Childhood‐onset epilepsy five decades later. A prospective population‐based cohort study. (4th October 2015) - Sillanpää, Matti; Anttinen, Anu; Rinne, Juha O.; Joutsa, Juho; Sonninen, Pirkko; Erkinjuntti, Matti; Hermann, Bruce; Karrasch, Mira; Saarinen, Maiju; Tiitta, Petri; Shinnar, Shlomo
Summary: Objective: To study the impact of childhood‐onset epilepsy on a variety of outcomes across the life span. Methods: A population‐based cohort of 245 subjects with childhood‐onset epilepsy was assessed for outcomes at 45 years. In addition, 51 of 78 surviving subjects with uncomplicated epilepsy and 52 of 99 originally matched controls participated in a detailed evaluation including electroencephalography (EEG), imaging, and laboratory studies at 50 years. Results: Of 179 surviving subjects, 61% were in terminal 10‐year remission and 43% in remission off medications. At 45 years, 95% of the idiopathic group, 72% of the cryptogenic group, and 47% of the remote symptomatic group were in terminal remission (p < 0.001). Abnormal neurologic signs were significantly more common in subjects with uncomplicated epilepsy than in controls. Mortality during period 1992–2012 was higher in subjects than in controls (9% vs. 1%, p = 0.02). The rate of 3T MRI abnormalities was higher in subjects than in controls (risk ratio [RR] 2.0; 1.3–3.1) specifically including findings considered markers of cerebrovascular disease (RR 2.5; 1.04–5.9). Even subjects with idiopathic epilepsy had higher rates of imaging abnormalities than controls (73% vs. 34%, p = 0.002). Significance: Long‐term seizure outcomes are excellent and a function of etiology. The presence of imaging abnormalities suggestive of vascular disease may put these subjects at higher risk for clinically evident stroke and cognitive changes as they age.